(untitled) (Central Medical College Journal, 2024)
Background: According to the research, despite the prevalence of allergic rhinitis (AR), it is frequently misdiagnosed or undertreated about its pattern, severity and risk factors. Aim: This study investigated the pattern, severity, and illness features of AR in Cumilla, Bangladesh, as well as symptom-relieving coping strategies among adult population. Methods: We conducted a quantitative observational descriptive cross-sectional study on outpatients from the ENT department of Central Medical College Cumilla, Bangladesh, between January 2020 and February 2023. Initially the sample size was 2949 and finally n= 2,549 participants selected who experienced at least one of the four symptoms of AR, namely runny nose, sneezing, nasal blockage, itchy nose, and watery eyes, unrelated to a cold or flu in the prior year. The study’s results were the triggers, pattern, severity, categorization of AR (2016 ARIA criteria), and coping strategies. We did descriptive statistics, univariate analytic statistics, and binary analysis. At <0.05, the P-value was deemed statistically significant. Results: The top AR trigger was dust (58.8%, n = 1500), followed by pollen (15.7%, n = 400), mold (11.88%, n = 300), and fur/perfumes (5.9%, n = 150). The prevalence of intermittent AR was 56 % (n = 1,435) and 44 percent (n = 1,114) for permanent AR. Nearly one-third (n = 816; 32%) complained of mild forms of AR, while the remainder (n = 1733; 68%) complained of moderate to severe types. The most common coping mechanisms were antihistamines (1649; 64.66%) and herbal hot liquids (185). (7.25%). Conclusion: This study examined the patterns, illness features, and related variables of self-reported AR in Cumilla, Bangladesh. Younger age groups and obese individuals who have reported chronic forms of AR should be given special consideration. Males reported more chronic and severe cases of AR. Central Medical College Journal Vol 7 No 2 July 2023 Page: 97-107